Interdigital-gated HEMT structure for high frequency devices - Hashim, Abdul Manaf; Kasai, Seiya; Hashizume, Tamotsu; Hasegawa, Hideki (2006)
Interdigital-gated AlGaAs/GaAs high electron mobility transistor (HEMT) structure was used to investigate the interaction between the drifting carrier plasma waves and electromagnetic (EM) waves. It was shown theoretically that the interaction in the range from microwave to terahertz (THz) at room temperature should produce negative conductance characteristics when the carrier drift velocity slightly exceeds the phase velocity of EM waves. S-parameter reflection measurements were carried out at room temperature for a frequency range from 1 to 20 GHz and a drastic change in conductance was observed at 5GHz and 10GHz with the increase of drain-source voltage. Large conductance change over 1000 mS/mm was obtained and it showed a peak at a certain frequency. The peak position could be controlled by changing the pitch size of the interdigital gates. These characteristics can be used for high frequency applications such as high-speed switching devices although a feature size of our interdigital-gated HEMT device is much larger than conventional HEMT device.